PENGEMBANGAN MEDIA PEMBELAJARAN MODUL ELEKTRONIK MATA KULIAH DIAGNOSIS KENDARAAN DI PROGRAM STUDI PENDIDIKAN TEKNIK MESIN UNIVERSITAS SRIWIJAYA (Program Studi Pendidikan Teknik Mesin Fakultas Keguruan dan Ilmu Pendidikan Universitas Sriwiajaya, 2017)
This research is a research & development (R & D). This study aims to produceinstructional media electronics module subjects Diagnosis Vehicle programmed studyMechanical Engineering Education Sriwijaya University in the form of electronic medialearning valid and practical serts have a potential effect, then that would be applied as a mediumof learning both on campus and outside campus. The research location is programmed studyMechanical Engineering Education sriwijaya university in the academic year 2016/2017 in 2014Inderalaya students. Media validity was assessed by two experts, namely, validation matterexperts and media experts. The validity of the material to get 87.96% of the categorized resultsare very valid, the validity sedangan media get 85% were categorized as very valid too. Followedby a one to one interview, in which the comments of the media is very positive, the next to seethe practicality do small group stage, the result is 83.84% of the results included practical. , Inthe field test results received n-gain of 0.90 and in the high category. It can be concluded thatthe electronic module Vehicle Diagnosis is valid, practical, and have a potential effect.